'n Dekonstruksie van 'n teks uit Die ongedanste dans van Breyten Breytenbach - Vorster, Anton Ferreira (Rhodes University, Faculty of Humanities, School of Languages, 1988)
The thesis provides an interpretation of the poem Êº(Taalstryd)Êº (Lewendood, p.143) by employing deconstruction theory, particularly as it has been developed by Jacques Derrida. The main assumption is that the text is not a self-sufficient entity, but finds itself in a continually changing relationship with other texts, a relationship described by deconstructionists as intertextuality. This relationship, as it has been described by Julia Kristeva, does not only involve literary works, but also the world-as- text. In chapter one this point of view is illustrated in a discussion around the title of the poem. It is postulated that the title is not a neutral description of a period in the history of the development of the Afrikaans language. Rather, it represents an ideological concept which can be interpreted in various ways. The poem clearly lends itself to an interpretation of "the struggle for the Taal" as a struggle which has manifested itself in many different areas and historical periods within the South African context. In chapter two the discussion of the relationship between language, history and ideology is continued. It is shown how the ÊºofficialÊº history represents a one-sided view of Afrikaans as a ÊºEuropeanÊº language, greatly ignoring its African component. This representation relies on a logocentric approach to the relationship between language and writing. Breytenbach's poetry, like the writings of Derrida, can be regarded as a "deconstruction" of this approach. The ÊºdisseminationÊº of meaning in Êº(Taalstryd)Êº is illustrated in terms of the poem's intertextual relationship with BreytenbachÊ¾s ÊºPlease don't feed the animalsÊº and KrigeÊ¾s ÊºLied van die Fascistiese bomwerpersÊº. Chapter three sets Êº(Taalstryd)Êº within the current debate surrounding Afrikaner survival. It is shown how the Afrikaner power base has been established and strengthened by way of legislation, the system of Christian National Education, as well as the creation of a nationalist-orientated history. This power base is currently in a state of crisis, in which different political groupings are continuing the Êº(Taalstryd)Êº
Keywords: Breytenbach, Breyten -- Criticism and interpretation